Revisit Intention Muslim Tourists to Halal Tourism in Yogyakarta: Analysis of Facilities, Promotion, Electronic Word of Mouth, and Religiosity - Juliana, Juliana; Syiva, Asyhari Nadzilla; Rosida, Rida; Permana, Erwin; Zulfikar, Rakhmat Muhammad; Abduh, Muhammad; Inomjon, Qudratov (Universitas Pendidikan Indonesia, 2024)
Purpose – To determine the influence of facilities, level of promotion, Electronic Word of Mouth, and religiosity on revisit intention halal tourism in Yogyakarta through consumer satisfaction as an intervening variable.Design/methodology/approach – This research uses quantitative methods with a causality approach. The analysis technique used was Structural Equation Modeling-Partial Least Square- (SEM-PLS) with a sample of 287 respondents.Finding – The research results show that the variables of facilities and consumer satisfaction have a positive effect on interest in returning to halal tourism in Yogyakarta. Meanwhile, the level of promotion, EWOM, and religiosity have no effect on Revisit intention halal tourism in Yogyakarta. As for mediation, the variable level of consumer satisfaction is only able to mediate the variables of facilities, level of promotion and electronic word of mouth on interest in repeat visits.Practical implications – this research finds that external factors and internal factors in consumer behavior, namely facilities and consumer satisfaction, play an important role in determining Revisit intention halal tourism in Yogyakarta. Therefore, the Yogyakarta provincial government, actors in the Yogyakarta tourism sector need to make efforts to increase interest in returning Muslim tourists to halal tourism in Yogyakarta.Originality/value – This research is the first to examine the influence of facilities, level of promotion, electronic word of mouth, and religiosity on interest in returning to halal tourism in Yogyakarta through consumer satisfaction as a mediator variable.